2018
DOI: 10.1021/acsbiomaterials.8b01146
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Stromal Cell-Derived Factor-1α in Three-Dimensional Hydroxyapatite/Polyacrylonitrile Composite Scaffolds for Bone Regeneration

Abstract: Bone regeneration strategies rely on biomaterial constructs with stem cells or growth factors. By comparison, cell homing strategies employ chemokines to recruit the host endogenous stem or progenitor cells to the defect site to support endogenous healing. In the present study, we used a novel fluffy hydroxyapatite/polyacrylonitrile (HA/PAN) composite scaffold to provide a better three-dimensional cell culture microenvironment. These HA/PAN composite scaffolds loaded with stromal cell-derived factor-1α (SDF-1α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Several studies have confirmed the superiority of MSCs homing in improving the quantity and efficacy of regeneration of different tissues ( Karp and Leng Teo, 2009 ; Xiang et al, 2020 ; Chen et al, 2021 ). For instance, Wang succeeded in BMSCs recruitment and osteogenic differentiation by loading hydroxyapatite/polyacrylonitrile scaffolds with SDF-1 ( Wang et al, 2019 ). Moreover, patients with GCs-ONFH present a decreased number of BMSCs in the lesion area ( Hernigou et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the superiority of MSCs homing in improving the quantity and efficacy of regeneration of different tissues ( Karp and Leng Teo, 2009 ; Xiang et al, 2020 ; Chen et al, 2021 ). For instance, Wang succeeded in BMSCs recruitment and osteogenic differentiation by loading hydroxyapatite/polyacrylonitrile scaffolds with SDF-1 ( Wang et al, 2019 ). Moreover, patients with GCs-ONFH present a decreased number of BMSCs in the lesion area ( Hernigou et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has prompted scientists to investigate the functionality of biomaterials incorporating SDF-1 as an artificial niche to recruit local MSCs. 152 The combination of SDF-1 with biomaterials is one of the most widely studied approaches to recruit different types of endogenous stem cells. For instance, it can be loaded into polyelectrolyte complex nanoparticles and encapsulated within gelatin hydroxyphenyl propionic acid hydrogels to be injected into brain lesions for recruiting local neural progenitor cells.…”
Section: Biomaterials As De Novo Niches For Homing Of Endogenous Mscsmentioning
confidence: 99%
“…4,5 Polymers such as chitosan (CS), cellulose, silk fibroin (SF), polyethylene glycol (PEG), polycaprolactone, polyurethanes, poly(lactic acid) (PLA), polyetheretherketone (PEEK), polyethylene (PE), polysulfone (PS), and polyacrylonitrile (PAN) are the most prominent polymers used for bone regeneration applications. 6 Among these polymers, polyacrylonitrile (PAN) is a synthetic polymer widely used for scaffold preparation, replacement of tissues, 7 and other medical devices because of its unique properties, such as mineral depositions on the pores, which help in developing the cells on scaffolds. Despite their properties, disadvantages such as a low degradability rate and a higher hydrophobic surface are associated with PAN.…”
Section: Introductionmentioning
confidence: 99%